Compressive behaviour and energy absorption of aluminium foam sandwich - Endut, N A; Al Hazza, Muataz Hazza Faizi; Abdullah Sidek, 'Atiah; Adesta, Erry Yulian Triblas; Ibrahim, N A (IOP Publishing, 2018)
Development of materials in automotive industries plays an important role in order to retain the safety, performance and cost. Metal foams are one of the idea to devolve new material in automotive industries since it can absorb energy when it deformed and good for crash management. Recently, new technology had been introduced to replace metallic foam by using aluminium foam sandwich (AFS) due to lightweight and high energy absorption behaviour. Therefore, this paper provides reliable data that can be used to analyze the energy absorption behaviour of aluminium foam sandwich by conducting experimental work which is compression test. Six experiments of the compression test were carried out to analyze the stress-strain relationship in terms of energy absorption behavior. The effects of input variables include varying the thickness of aluminium foam core and aluminium sheets on energy absorption behavior were evaluated comprehensively. Stress-strain relationship curves was used for energy absorption of aluminium foam sandwich calculation. The result highlights that the energy absorption of aluminium foam sandwich increases from 12.74 J to 64.42 J respectively with increasing the foam and skin thickness.